2022
DOI: 10.1172/jci.insight.152631
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of TCR Vβ-Jβ profile for adjuvant gefitinib in EGFR mutant NSCLC from ADJUVANT-CTONG 1104 trial

Abstract: Herein, we characterize the landscape and prognostic significance of the T cell receptor (TCR) repertoire of early-stage non–small cell lung cancer (NSCLC) for patients with an epidermal growth factor receptor ( EGFR ) mutation. β Chain TCR sequencing was used to characterize the TCR repertoires of paraffin-preserved pretreatment tumor and tumor-adjacent tissues from 57 and 44 patients with stage II/III NSCLC with an EGFR mutation treated with gefitinib or chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…We described the positive or negative association of special TCR rearrangements with clinical outcomes and their role for potential guiding adjuvant TKI or chemotherapy decisions in EGFR ‐mutant NSCLC patients (Figure 1). As expected, low TCR repertoire diversity was significantly associated with poor overall survival (OS) in early‐stage NSCLC patients with an EGFR mutation 9 . Of note, we identified four special TCR Vβ‐Jβ rearrangements associated with favourable OS, which may have an anti‐tumour response to NSCLC.…”
Section: Figuresupporting
confidence: 68%
“…We described the positive or negative association of special TCR rearrangements with clinical outcomes and their role for potential guiding adjuvant TKI or chemotherapy decisions in EGFR ‐mutant NSCLC patients (Figure 1). As expected, low TCR repertoire diversity was significantly associated with poor overall survival (OS) in early‐stage NSCLC patients with an EGFR mutation 9 . Of note, we identified four special TCR Vβ‐Jβ rearrangements associated with favourable OS, which may have an anti‐tumour response to NSCLC.…”
Section: Figuresupporting
confidence: 68%
“…A total of 356 distinct TCR rearrangements were identified. 8 Notably, Vβ6‐6Jβ1‐3 and Vβ6‐6Jβ1‐6 demonstrated statistical significance in predicting poor overall survival (OS) (FDR adjusted p < .05, Figure 1A ). Importantly, the combination of Vβ6‐6Jβ1‐3 and Vβ6‐6Jβ1‐6 was the best model in predicting OS (Figure 1B ), which was internally validated by 100 repeated 10‐fold cross‐validation (Figure S3) .…”
Section: Figurementioning
confidence: 97%
“…We also discovered that our previously identified chronic myeloid leukemia (CML)-associated TCR Vβ clone specifically recognizes Wilm’s tumor 1 (WT1) antigenic peptides by stimulating T cells in healthy donors with MHC-restricted antigenic peptides and TCR Vβ gene sequencing [ 26 ]. Recently, our team and partners have also found TCR Vβ clones that are closely related to the prognosis of lung cancer patients [ 27 ]. Our team recently analyzed the TCR Vα and Vβ chain genes of T cells from B cell-acute lymphoid leukemia (B-ALL) patients by single-cell sequencing and found that the patients’ T cells had polyclonal subtypes, and most of them were effector subsets [ 28 ].…”
Section: Tcr-t Cell Constructionmentioning
confidence: 99%
“…The result of this study contributes to a better understanding of the role of TCR-T cell therapy in NSCLC. In the clinical trial CTONG 1104, our team and partners found that TCR Vβ5–6 Jβ2 − 1, TCR Vβ20 − 1 Jβ2 − 1, and TCR Vβ24 − 1 Jβ2 − 1 in NSCLC patients with an EGFR mutation were associated with good overall survival (OS) in the gefitinib group, while TCR Vβ29 − 1 Jβ2–7 was related to good OS in the conventional chemotherapy group [ 27 ]. These results suggested that TCR-T cells, based on these specific TCRs and combined with existing targeted therapies, may benefit more NSCLC patients.…”
Section: Tcr-t Cell Constructionmentioning
confidence: 99%
See 1 more Smart Citation